Illegal Unreported and Unregulated (IUU) Fishing: Upaya Mencegah dan Memberantas Illegal Fishing dalam Membangun Poros Maritim Indonesia - Abdul Qodir Jaelani (UIN Sunan Kalijaga Yogyakarta, 2014)
Indonesia has had some legislation as the legal basis on which the prevention anderadication of illegal fishing in Indonesia thats include the Territorial Sea Act 1939and the Maritime Environment (Territorial Zee en Maritime Kringen Ordonantie,Stbl.1939 No. 442), UU No. 17 of 1985 on the Ratification of the United NationsConvention on the Law of the Sea (UNCLOS), UU No. 5 of 1983 on theIndonesian Exclusive Economic Zone, Act No. 21 of 1992 on Shipping, UU No. 6of 1996 About Indonesian water , UU No. 31 Year 2004 jo. Act No. 45 of 2009on the Fisheries Act No. 32 of about Marine, Regulation of the Minister of Marineand Fisheries of the Republic of Indonesia Number 2 / CANDY-KP / 2015 on theProhibition of the Use of Fishing Trawler and trawl Pull in Regional FisheriesManagement of the Republic of Indonesia. But the reality in Indonesia is still a lot ofcases of illegal fishing going on, it can be seen from the development of Non-TaxRevenues from KP sector fluctuated. In 2012, the Supreme Audit Agency (BPK)estimates of IUU fishing state losses of Rp 300 trillion and cause damage to habitatsand marine ecosystems. Including illegal fishing that accompanied the destruction of themarine environment either by blast fishing, trawling, and using cyanide.